Aesthetics and the orofacial harmonization (Research, Society and Development, 2023)
The aging process affects all structures of the face, however, the onset and speed of changes vary between each specific structure, individual and different ethnic groups. Therefore, knowledge of aging-related anatomy is crucial for the work of an orofacial harmonization specialist when performing a procedure aimed at restoring facial structures and providing a more youthful appearance. This review aims at the current understanding of human facial anatomy and seeks to clarify the transformations that occur in bones, ligaments, muscles, fat and skin during aging. In addition, the role played by the professional in the area of orofacial harmonization in rejuvenating treatments, including the use of botulinum toxin and facial fillers, with an emphasis on hyaluronic acid, is highlighted.